Phenotypic expression of HbO Indonesia in two Indian families and its interaction with sickle hemoglobin - Amar Das Gupta; Anita Nadkarni; Pallavi Mehta; Manju Goriwale; Manisha Ramani; Pradnya Chaudhary; Vishal Mehrotra; Roshan Colah (Wolters Kluwer Medknow Publications, 2017)
Background: Alpha globin chain variants are clinically significant since they directly influence the structure and function of the hemoglobin (Hb) molecules they constitute, either in combination with normal beta globin chains or with variant beta chains, thereby altering the morbidity and mortality associated with the resultant hemoglobinopathies. We describe here two unrelated families from Madhya Pradesh who had a nondeletional alpha-chain variant, HbO Indonesia (CD116 G → A). Members of one of the two families also had coinheritance of sickle hemoglobin (HbS). Aims: The aim was to study the phenotype of HbO Indonesia and its interaction with HbS. Materials and Methods: Hb electrophoresis, high-performance liquid chromatography (HPLC), covalent reverse dot blot hybridization, amplification refractory mutation system, multiplex polymerase chain reaction, and direct gene sequencing were used to identify and characterize the variant Hbs. Results: The abnormal Hb moved in HbS region in Hb electrophoresis at alkaline pH but gave an abnormal peak in HPLC with a retention time (RT) of 4.86-4.89 min. In two members of the family with coinheritance of HbS, it produced small additional abnormal Hb peaks (4.6% in heterozygous and 11.9% in homozygous member) in HPLC with a longer RT (5.15-5.17 min) possibly resulting from a combination of HbO Indonesia alpha chain with HbS beta chain. Conclusions: It appears that depending on the zygosity of HbS, HbO Indonesia would subtract a variable amount of HbS beta chain from the total pool, thereby potentially reducing the clinical severity of HbS disease. HbO Indonesia per se does not cause anemia or alter the red cell indices.